2009
DOI: 10.1007/s11947-009-0200-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flour and Extruded Noodles from Eight Cassava Mosaic Disease (CMD)-Resistant Varieties

Abstract: Flours processed from eight cassava roots were selected from recently developed Cassava Mosaic Disease resistant varieties (92b/00061, 95/0289, 92/0057, 96/1632, 98/0505, 97/2205, TME419 and 92/0326). They were evaluated for proximate composition, hydrogen cyanide, vitamin A and functional properties. They were also processed into noodles adapting a locally fabricated cold extruder as a single-screw extruder. The extruded cassava noodles were cooked and subjected to sensory analysis. Principal component and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Highest carbohydrate (CHO) content was observed in flour packed in paper bag for both cultivars (83.9 ± 0.14 for “TME 419ˮ and 86.4 ± 0.14% for “UMUCASS 36ˮ) at 23°C and 60% RH storage condition. The percentage CHO contents were within the range (84.1 ± 0.06% to 85.4 ± 0.07%) reported for cassava flour cultivars (92b/00061, 95/0289, 92/0057, 96/1632, 98/0505, 97/2205, TME 419, and 92/0326) by Nwabueze and Anoruoh (). A slight increase in dry matter content was observed for “UMUCASS 36,ˮ while “TME 419ˮ was unchanged at the end of the 12 wk storage period in all the packaging materials.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Highest carbohydrate (CHO) content was observed in flour packed in paper bag for both cultivars (83.9 ± 0.14 for “TME 419ˮ and 86.4 ± 0.14% for “UMUCASS 36ˮ) at 23°C and 60% RH storage condition. The percentage CHO contents were within the range (84.1 ± 0.06% to 85.4 ± 0.07%) reported for cassava flour cultivars (92b/00061, 95/0289, 92/0057, 96/1632, 98/0505, 97/2205, TME 419, and 92/0326) by Nwabueze and Anoruoh (). A slight increase in dry matter content was observed for “UMUCASS 36,ˮ while “TME 419ˮ was unchanged at the end of the 12 wk storage period in all the packaging materials.…”
Section: Resultssupporting
confidence: 71%
“…High quality cassava flour (HQCF) is a potential product for composite flour in baking of bread. Studies have shown that cassava flour is a good substitute for wheat flour in food processing (Nwabueze and Anoruoh ). This is attributed to its high energy value, gluten free nature, low cost of production and availability (Gyedu‐Akoto and Laryea ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to regular food products, basic ingredients in extruded food may be derived from various sources, which can be combined to contain all necessary micronutrients, flavours and colours. (Nwabueze and Anoruouh 2009). Snack foods are one of the fastest-growing branches of food industry.…”
Section: Introductionmentioning
confidence: 99%
“…Cassava root produces excellent flour quality and therefore has been promoted as composite flour for use in the food industries (Shittu et al 2008;Nwabueze and Anoruoh 2009). Cassava flour is highly recommended in the diet of celiac patients with strict adherence to gluten-free food products (Briani et al 2008;Niewinski 2008).…”
Section: Economic Importance Of Cassavamentioning
confidence: 99%